Interferon-γ stimulates human follicular dendritic cell-like cells to produce prostaglandins via the JAK-STAT pathway. Issue 2 (August 2015) - Kim, Jini; Yoon, Yongdae; Jeoung, Dooil; Kim, Young-Myeong; Choe, Jongseon
Highlights Interferon-γ enhances COX-2 expression in human follicular dendritic cell-like cells. STAT1 is indispensable for the interferon-γ-induced COX-2 expression and prostaglandin production. Both JAK1 and JAK2 are required for the interferon-γ-induced COX-2 expression and prostaglandin production.